Prevalence of canine cranial cruciate ligament rupture and prognosis depending on tibial plateau angle: A retrospective study. - Seo, Beom-Seok; Park, Chul; Rahman, Md Mahbubur; Jeong, Inseong; Kim, Namsoo (Journal of Advanced Veterinary and Animal Research, 2024)
Objective: This study aimed to evaluate the prevalence of cranial cruciate ligament rupture (RCCL) and the efficacy of tibial plateau angle (TPA) as a prognostic indicator in small breed dogs diagnosed with RCCL. Materials and Methods: For this study, 53 dogs with RCCL were selected based on their medical data. The Tibial plateau angle (TPA) was calculated by analyzing the radiographic images of the stifle joint region. The dogs were categorized based on their body weight, sex, age, breed, and RCCL. Subsequently, clinical outcomes of dogs were evaluated based on their pre- and postoperative TPAs. Results: The prevalence of RCCL was higher in neutered dogs, especially those neutered before 6 months of age. The preoperative TPAs of all dogs diagnosed with RCCL were lowered with TPLO. Preoperative walking time in the higher pre-operative TPA (>25°) group (13.58 ± 1.53 days) was significantly (p < 0.05) longer than the lower pre-operative TPA (≤25°) group (10.09 ± 0.84). The lower pre-operative TPA (≤ 25°) group showed better prognoses without any more complications than the higher pre-operative TPA (> 25°) group. Furthermore, post-operative walking time in the higher post-operative TPA dogs (>10°) group (18.08 ± 2.22 days) was significantly (p < 0.05) longer than the lower post-operative TPA dogs (≤10°) group (10.20 ± 0.90 days). Likewise, the TPA (≤10°) group showed better prognoses with lowered complications. Conclusion: Therefore, pre- and post-operative TPA plays an important prognostic factor, and post-operative TPA should be kept at<10° to get better clinical outcomes.> <10° to get better clinical outcomes. J. Adv. Vet. Anim. Res., 11(3): 627–636, September 2024 http://doi.org/10.5455/javar.2024.k812